ASSESSMENT OF THE RISK FACTORS ASSOCIATED WITH AFLATOXIN CONTAMINATION DURING THE MARKETING OF PEANUTS IN CÔTE D'IVOIRE - Ama Léthicia MANIZAN (Stefan cel Mare University of Suceava, 2018)
This study was conducted to assess the different risk factors related to practices of sale of peanuts for better control of aflatoxin contamination and also to improve the safety of peanuts during marketing. The sales practices are similar regardless of the area surveyed. Of all the respondents in this survey, 61.7% were men as against 38.3% women and 70% of the respondents do not have any formal education. The marketing of peanut seeds is generally an activity done by men (100%) while that of peanut paste is assigned to women (100%). The unsold peanut paste is kept from 1 day to 3 months at room temperature until sale, mainly in market stalls used to sell it (42.4%) or in stores (39.4%). The losses are mainly due to fungi (37.9%) and insects (13.6%) followed by humidity and high temperature (4.5%). During sale of peanut paste, the site, the surroundings of sales points and the storage containers are potential fungi growth factors and eventual risk points for mycotoxin contamination. Proper handling and hygiene might reduce the aflatoxin contamination of peanut to ensure better sanitary quality of peanuts and protect consumer’s heath.